2019
DOI: 10.1039/c9nj02556a
|View full text |Cite
|
Sign up to set email alerts
|

The development of a novel biosensor based on gold nanocages/graphene oxide–chitosan modified acetylcholinesterase for organophosphorus pesticide detection

Abstract: In this work, a novel acetylcholinesterase biosensor, namely, gold nanocages/graphene oxide–chitosan nanocomposite modified screen-printed carbon electrode was prepared for chlorpyrifos detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 53 publications
0
15
0
4
Order By: Relevance
“…These structures are produced by galvanic replacement reaction, resulting in assemblies with unique and tunable properties. Compared to the solid nanoparticles, both inner and outer surfaces of gold nanocages (AuNCs) provide good electron transfer from the aptamers’s (short DNA or RNA fragments) redox center to the surface electrode [ 48 ].…”
Section: Spes Modification With Morphologically Different Nps Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…These structures are produced by galvanic replacement reaction, resulting in assemblies with unique and tunable properties. Compared to the solid nanoparticles, both inner and outer surfaces of gold nanocages (AuNCs) provide good electron transfer from the aptamers’s (short DNA or RNA fragments) redox center to the surface electrode [ 48 ].…”
Section: Spes Modification With Morphologically Different Nps Systemsmentioning
confidence: 99%
“…Yao et al [ 48 ] developed a new biosensor to detect chlorpyrifos, an extensively used organophosphate pesticide in agriculture [ 95 ]. Firstly, a nanocomposite was constructed of graphene oxide (GO), chitosan (CS), and the AuNCs.…”
Section: Spes Modification With Morphologically Different Nps Systemsmentioning
confidence: 99%
“…Although a lot of work has already been reported on graphene-based biosensors; however, due to novel microbes and diseases associated with them, excess use of toxicants in food and feed products, nonjudicial use of pesticide and day by day disintegrating environmental conditions urgently need tools for detection of such chemicals and biologicals, and hence, more rapid and urgent requirement for the development of biosensors arises In the past 2 years, countless new graphene oxide nanohybrids-based biosensors are reported. For example, Yao et al [147] reported an electrochemical biosensor based on the inhibition of AChE, using a gold nanocage/graphene oxide-chitosan nanocomposite-modified screen-printed carbon electrode for detection of chlorpyrifos (Figure 2). Where the biosensor showed good electrocatalytic activity for the oxidation of enzymatically produced thiocholine and detected chlorpyrifos concentrations as low as 3 ng L −1 .…”
Section: Graphene Oxide-based Nanohybrids As Pesticide Biosensorsmentioning
confidence: 99%
“…(a) A schematic diagram of the construction process of AChE biosensor based on screen-printed electrodes, (b) and (c) DPV behavior, and percent inhibition obtained by biosensor in the presence of chlorpyrifos.Reprinted with permission from ref [147],. published by the Royal Society of Chemistry (RSC) on behalf of the Centre National de la Recherche Scientifique (CNRS) and the RSC.…”
mentioning
confidence: 99%
“…Such an increase in the PL behavior of GO and its physisorbed or chemically modified derivatives have been used for diverse sensing applications. [20][21][22][23] Recently, the chemosensor application of GO-derived materials has been continuously explored in the detection of heavy metal ions 24 and even for f-block elements, 25 organophosphorus pesticides, 26 and ATP and GTP monitoring in living cells. 27 A maximum number of reports have focused on the quenching of the PL through either blocking or unblocking of the graphitic surface of GO through physisorbed molecules over the surface 28 or decorated nanoparticles.…”
Section: Introductionmentioning
confidence: 99%